Pendampingan Mata Pelajaran Sejarah dalam Meningkatan Literasi Membaca Siswa di SMA Negeri 3 Pematangsiantar - Hasugian, Jalatua Habungaran; Damanik, Robinson (Mitra Abdimas: Jurnal Pengabdian kepada Masyarakat, 2023)
This research discusses the reading literacy mentoring for students at SMA Negeri 3 Pematangsiantar through the history subject. The low interest in reading among students in Indonesia can lead to stagnant educational quality. The mentoring program includes strategies such as integrating reading literacy into history lessons, providing relevant reading materials, using active learning techniques, involving the local community, mentoring students, and utilizing digital technology. Despite challenges such as limited resources and low reading interest, this mentoring program aims to improve students' reading skills and enhance their understanding of history.